2011
DOI: 10.1134/s1021443712010050
|View full text |Cite
|
Sign up to set email alerts
|

CLE peptides are universal regulators of meristem development

Abstract: Meristems are morphogenic plant tissues comprising the pool of stem cells initiating specialized tissues. The balance of stem cell proliferation and differentiation depends on antagonistic action of genes WOX encoding homeodomain containing transcription factors and CLAVATA like systems controlling their expression. The CLE (CLAVATA3/ENDOSPERM SURROUNDING REGION) peptides and their recep tor protein kinases comprise the basis of the CLAVATA like systems. Definite member of the family of CLE peptides (CLV3 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…By binding to its receptors, the CLAVATA1 like Ser Thr kinases, CLE peptides trigger the poorly investigated signaling pathway that regulates the expression of WOX genes (in most cases, negatively). Thus, CLE peptides, their receptors, and the regulated WOX genes form the so called WOX-CLAVATA sys tems [48] (similarly to the previously identified WUS-CLAVATA system, regulating SAM development) [49]. Regulation of WOX expression by CLE peptides takes place in the control of meristem activity and in embryogenesis.…”
Section: Wox Tfmentioning
confidence: 99%
“…By binding to its receptors, the CLAVATA1 like Ser Thr kinases, CLE peptides trigger the poorly investigated signaling pathway that regulates the expression of WOX genes (in most cases, negatively). Thus, CLE peptides, their receptors, and the regulated WOX genes form the so called WOX-CLAVATA sys tems [48] (similarly to the previously identified WUS-CLAVATA system, regulating SAM development) [49]. Regulation of WOX expression by CLE peptides takes place in the control of meristem activity and in embryogenesis.…”
Section: Wox Tfmentioning
confidence: 99%
“…Many studies have demonstrated that WUSCHEL-RELATED HOMEOBOX ( WOX ) transcription factors are involved in controlling the early stages of embryogenesis, the maintenance of meristem activity, and the formation of lateral organs, such as lateral roots, leaves, and floral primordia 1 , 2 . Moreover, it has been reported that the action of WOX s is regulated by CLE peptides (CLAVATA3/EMBRYO SURROUNDING REGION-RELATED) 3 and by the two major plant hormones: (1) auxins in the root apical meristem (RAM) and the cambium, and (2) cytokinins in the shoot apical meristem (SAM) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Many other CLE genes and proteins have been investigated, mostly in Arabidopsis. CLV3 functions in shoot apical meristem maintenance through a signaling pathway that involves CLAVATA1 (CLV1) and BARELY ANY MERISTEM (BAM1-3) receptors, CLAVATA2/ CORYNE-SOL2 and RPK2 coreceptors and the WUSCHEL (WUS) transcription factor (reviewed in Dodueva et al, 2012;Miyawaki et al, 2013;Somssich et al, 2016). Using a similar signaling cascade, CLE40 regulates root apical meristem cell homeostasis via the Arabidopsis CRINKLY4 (ACR4) receptor and WUSCHEL-LIKE HOMEOBOX5 (WOX5) (reviewed in De Smet et al, 2008;Stahl et al, 2009;Dodueva et al, 2012;Kiyohara & Sawa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…CLV3 functions in shoot apical meristem maintenance through a signaling pathway that involves CLAVATA1 (CLV1) and BARELY ANY MERISTEM (BAM1-3) receptors, CLAVATA2/ CORYNE-SOL2 and RPK2 coreceptors and the WUSCHEL (WUS) transcription factor (reviewed in Dodueva et al, 2012;Miyawaki et al, 2013;Somssich et al, 2016). Using a similar signaling cascade, CLE40 regulates root apical meristem cell homeostasis via the Arabidopsis CRINKLY4 (ACR4) receptor and WUSCHEL-LIKE HOMEOBOX5 (WOX5) (reviewed in De Smet et al, 2008;Stahl et al, 2009;Dodueva et al, 2012;Kiyohara & Sawa, 2012). Arabidopsis CLE41/44 were originally identified as tracheary element differentiation inhibitory factors (TDIF); they inhibit cell differentiation and promote procambium cell proliferation through the TDIF RECEPTOR (TDR, also called PHLOEM INTERCALATED WITH XYLEM, PXY) and WOX4 (reviewed in Dodueva et al, 2012;Kiyohara & Sawa, 2012;Hirakawa & Bowman, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation